Review and analysis of vertical siting requirements for piled piers of ports along Manila Bay - Bobiles, Kevin Nichole S.
Ports in the Philippines are required to have a minimum pier deck elevation according to tide levels and ship metrics (PPA, 2005) .However, the basis of such design requirement is not clear. The crown height of a pier is known to be affected by several factors, including tidal levels, wave conditions, and ocean hazards. In view of the susceptibility of the country to tropical cyclones, this study aims to assess the adequacy of the code requirement by reviewing the theory and numerical analysis of storm-induced ocean hazards. In relation to this, storm surge will be of utmost importance since this phenomenon generates water surface elevation in a worst case scenario along coastlines which greatly affects the vertical location of piled piers - an important input to the structural design of harbor facilities such as ports. Using the National Oceanic and Atmospheric Administration (NOAA) SLOSH model, a numerical simulation of storm surges due to historical typhoons is performed in the developed Philippine basin. The outputs of the SLOSH model, namely the envelopes of water surface, for each historical typhoon, and subsequently EOWs of all simulated historical typhoons are synthesize to yield the maximum envelope of water (MEOW) at the site basin. From these, historical storm surge heights can be determined and with some adjustment in the datum, the result of the simulation can now be compared with the vertical siting requirement of PPA.